The Effectiveness of the Combination of Snakehead Fish Extract and Acupresure on Albumin Conditions and Blood Pressure of Pregnant Women with Preeclampsia - Shandy Wigya Mahanani; Mardiyono Mardiyono; Imam Djamaluddin; Handayani Handayani (Journal Research of Social Science, Economics, and Management, 2022)
One of the causes of maternal death is preeclampsia. Preeclampsia and eclampsia are caused by factors that decrease serum albumin (hypoalbuminemia) which causes a decrease in intravascular hypovolemic pressure. This study aimed to evaluate the effectiveness of snakehead fish extract and acupressure on albumin levels and blood pressure in pregnant women with preeclampsia. The research method is a non-randomized pretest-posttest control group design study and was conducted at a health center in Central Java, Indonesia. A sample of 30 subjects; 15 subjects in the experimental group, and 15 subjects in the control group. The experimental group was given snakehead fish extract 2x 500 mg every day for 14 days and acupressure at points GV 20, Li 3, and Ki 3 6 times for 14 days. Systolic and diastolic blood pressure measurements were performed on day 1 and day 14. Data analysis used paired parametric t test. The results showed that snake head extract and acupressure for 14 days had a significant decrease in diastolic from 12 mmHg to 10.66 mmHg (p=0.000), while in the control group there was no decrease in systolic blood pressure of 0.667 (p=0.670) and systolic blood pressure was 0.667 (p=0.670). pressure 0.667 (p=0.670). diastolic 2.66 p=0.041. In the experimental group there was an increase in albumin levels of 1.12 (p = 0.000. In the control group, albumin levels were -0.14 before and after the measurement did not affect albumin levels with a value of p = 0.082. Giving snakehead fish extract and acupressure at the KI 3 point, LV3, and GV 20 were effective in increasing albumin levels and lowering blood pressure in preeclamptic women.